The most wanted: IELTS courses - Ezihaslinda, Ngah (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
28 June 2010. ‘A Course on IELTS’ is a popular and one of the most sought after in UMP, especially among academic staff. One of the main objectives of the course is to assist lecturers who intend to sit for IELTS for the purpose of pursuing studies at postgraduate levels or for UMP job confirmation. The course is jointly organised by the Modern Languages Department of CMLHS and the Human Resource Department.